IFN-γ/IL-2 Double-Color FluoroSpot Assay for Monitoring Human Primary T Cell Activation: Validation, Inter-Laboratory Comparison, and Recommendations for Clinical Studies - Alexandra Mauthe; Edward Cedrone; Raquel Villar-Hernández; Elisa Rusch; Marco Springer; Martin Schuster; Rosemarie Preyer; Marina A. Dobrovolskaia; Matthias Gutekunst (The AAPS Journal, 2025)
The enzyme-linked immunosorbent spot (EliSpot) assay and its fluorescence-based version, FluoroSpot, are sensitive immunoassays commonly used to quantify antigen-specific T and B lymphocytes and other immune cells in peripheral blood or homogenized tissues. Due to their high sensitivity, these assays are popular in clinical trials to evaluate the efficacy of immunotherapy and vaccines, which involve a high level of scrutiny to ensure valid study results. Besides industry consensus white papers and other research publications, there is no formal guidance for the industry on how to validate EliSpot and FluoroSpot assays to ensure their accurate performance for immune monitoring in clinical trials. Herein, we describe a comprehensive in vitro study using healthy human donor peripheral blood mononuclear cells (PBMCs) and model antigens to validate a double-color FluoroSpot assay for monitoring antigen-specific lymphocytes by detecting and quantifying IFN-γ and IL-2-producing lymphocytes. Validation parameters, acceptance criteria set-up, and assay limits—limit of detection (LOD), minimum positive control response, lower and upper limits of quantification (LLOQ and ULOQ)—were determined, and assay performance was demonstrated by assessing precision, specificity, linearity, and robustness. In addition, an inter-laboratory comparison demonstrated concordance between assay results from two laboratories. In summary, this study outlines a robust approach to EliSpot and FluoroSpot validation and demonstrates that the IFN-γ/IL-2 FluoroSpot assay is suitable for the reliable detection of antigen-specific immune responses from PBMC samples across laboratories and meets the current regulatory requirements for bioanalytical method validation. Graphical Abstract

Urgent plea for global protection of springs - Marco Cantonati; Roderick J. Fensham; Lawrence E. Stevens; Reinhard Gerecke; Douglas S. Glazier; Nico Goldscheider; Robert L. Knight; John S. Richardson; Abraham E. Springer; Klement Tockner (Conservation Biology, 2021)